2015
DOI: 10.1002/cctc.201500380
|View full text |Cite
|
Sign up to set email alerts
|

Surface Segregation of Fe in Pt–Fe Alloy Nanoparticles: Its Precedence and Effect on the Ordered‐Phase Evolution during Thermal Annealing

Abstract: Coupling electron microscopy techniques with in situ heating ability allows us to study phase transformations on the single-nanoparticle level. We exploit this setup to study disorder-to-order transformation of Pt–Fe alloy nanoparticles, a material that is of great interest to fuel-cell electrocatalysis and ultrahigh density information storage. In contrast to earlier reports, we show that Fe (instead of Pt) segregates towards the particle surface during annealing and forms a Fe-rich FeOx outer shell over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 58 publications
3
14
0
Order By: Relevance
“…3 (a) where such contrast extends out 0.6 nm or more. Most likely this is Fe-rich material as reported by Prabhudev et al [22]. The possibility that the Fe is oxidized cannot be excluded.…”
Section: Annealing At 500°csupporting
confidence: 51%
“…3 (a) where such contrast extends out 0.6 nm or more. Most likely this is Fe-rich material as reported by Prabhudev et al [22]. The possibility that the Fe is oxidized cannot be excluded.…”
Section: Annealing At 500°csupporting
confidence: 51%
“…[65] By controlling the H 2 reduction temperature and time, core-shell structured Pt-Pt 3 Co nanoparticles with 2-3 atomic-layer Pt shells (Pt 3 Co@Pt) could be obtained, [66] even Pt-skin on Pt 3 Co (or Pt 3 Ni) bimetallic materials. [69][70][71] Pt has negative segregation energy, and Ni (or Co) has positive segregation energy; hence, Pt tends toward surface segregation. [68] The precursor mixtures (containing Pt precursor and Ni precursor) usually are dispersed into solvents, and then these mixtures are ultrasonicated before the solvents evaporate.…”
Section: Chemical Methodsmentioning
confidence: 99%
“…Finally, by controlling the thermal treatment, Pt‐skin on well‐dispersed Pt 3 Ni bimetallic nanoparticles can be obtained. The reason why CTTM could tune the surface composition is that there is a general trend in the surface segregation phenomena in the bimetallic nanomaterials . Pt has negative segregation energy, and Ni (or Co) has positive segregation energy; hence, Pt tends toward surface segregation .…”
Section: Controlling the Surface Composition Of Ptm Bimetallicsmentioning
confidence: 99%
“…With high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) and EELS, we have studied the evolution of alloy catalysts following in-situ and ex-situ annealing procedures. Starting with a disordered PtFe nanoparticle, we captured the ordering transformation, showing evidence of ordered Pt and Fe rich planes formation, and evidence of both Pt and Fe-rich shells over a Pt-Fe ordered core ( Figure 1) [2]. We also showed that the Pt surface segregation induces local strain and atomic displacements [2] ( Figure 2) that can be further correlated to the enhanced catalytic activity of the material, in addition to the enhanced durability shown previously [3,4].…”
mentioning
confidence: 99%
“…Starting with a disordered PtFe nanoparticle, we captured the ordering transformation, showing evidence of ordered Pt and Fe rich planes formation, and evidence of both Pt and Fe-rich shells over a Pt-Fe ordered core ( Figure 1) [2]. We also showed that the Pt surface segregation induces local strain and atomic displacements [2] ( Figure 2) that can be further correlated to the enhanced catalytic activity of the material, in addition to the enhanced durability shown previously [3,4]. Using in-situ heating, and taking advantage of fast acquisition capabilities with EELS, it has also been possible to study the alloying phenomena of AuPt nanoparticles showing evidence of full miscibility starting at 200ºC (Figure 3), well below the thermodynamically expected temperature, due to the reduced scale of the system.…”
mentioning
confidence: 99%